The Healthy School Movement and Students’ Quality of Life: A CIPP Evaluation Study in Indonesian Secondary Education - Ita Rahmayanti; Kartini Kartini; Fatmaridah Sabani (Har Press Indonesia, 2026)
This study aims to evaluate the implementation of the Healthy School Movement (Gerakan Sekolah Sehat/GSS) in improving students’ quality of life at SMP Negeri 5 Palopo. The study employed a qualitative approach with a phenomenological design. Data were collected through observation, semi-structured interviews, and documentation involving the principal, teachers, school staff, and students. The study used the Context, Input, Process, and Product (CIPP) evaluation model developed by Daniel Stufflebeam as the analytical framework. Data analysis was conducted through data reduction, data display, and conclusion drawing. The findings revealed that the implementation of GSS was supported by institutional commitment, stakeholder participation, and school readiness in promoting healthy lifestyles. From the context aspect, the program addressed students’ low awareness regarding hygiene and environmental cleanliness. From the input aspect, the school demonstrated adequate organizational support, human resources, and supporting facilities, although infrastructure limitations remained. From the process aspect, GSS activities were implemented through healthy nutrition campaigns, environmental maintenance, physical exercise, and health education programs integrated into students’ daily routines. From the product aspect, the program contributed positively to improving students’ healthy behavior, environmental awareness, discipline, and school environmental quality. However, several challenges were identified, including limited facilities, inconsistent student awareness, and limited time allocation for program activities. This study concludes that the Healthy School Movement has significant potential to improve students’ quality of life through healthy behavioral development and supportive school environments. Sustainable collaboration, policy support, and infrastructure improvement are necessary to strengthen program effectiveness and sustainability.